Ottoman Book Collectors and Illustrated Sixteenth Century Shiraz Manuscripts - Laie Uluç (Revue des Mondes Musulmans et de la Méditerranée)
This article is a survey of the archival lists of holdings of private libraries of Ottoman intellectuals, bureaucrats and elite. It also examines the published evidence of such libraries and codi-cological evidence from the illustrated luxury editions of the works of classical Persian authors found in the Istanbul collections, as well as establishing the popularity of the Persian illustrated book in the Ottoman realm.